Effectiveness of "Healthy Living Training Program" on Obese Policemen - Rupali V. Sabale; Gajanan Velhal; Yashovardhan Kabra; Shilpa Nellikkal (Wolters Kluwer Medknow Publications, 2024)
Background: Considering the concerns of obesity problems, Mumbai Police authorities had launched full-day residential "Healthy Living Training Program" in February 2019 for obese policemen. We studied the effectiveness of the program by assessing health profile of the participants, and change in anthropometric measurements and blood pressure readings. Methods and Materials: Permission from the concerned authorities and approval from the Institutional Ethics Committee (IEC) were taken. Health profiles of 143 policemen were assessed. Anthropometric measurements and blood pressure recordings were done on the first and the last day of the 28-day program. The data were coded and entered in password-protected Microsoft Excel. Paired t-test was applied to test statistically significant differences. The association of some of the variables with weight change was assessed by the Chi-square test for categorical variables. Results: The mean age of participants was 49.6 ± 5 years. The proportion of hypertensive, diabetics, vision problems, and bone and joint problems were 48.2%, 23.2%, 57.1%, and 46.4%, respectively. Only 70% of them had home-cooked food in the lunch. Daily, 50% of the participants do physical activity. There was statistically significant weight reduction (105.6 ± 12.1s vs. 103.3 ± 12 kg), body mass index (BMI) (36.3 ± 3.4 vs. 35.5 ± 3.3), waist circumference (110.8 ± 7.9 vs. 109.5 ± 7.9), and hip circumference (115.6 ± 8.1 vs. 106.8 ± 15.0) of the participants after 28 days of training program. Conclusion: "Healthy Living Training Program" was effective in reducing weight, blood pressure, BMI, and waist and hip circumference. The program benefitted the participants by inculcating healthy lifestyles and raising awareness of health issues.